COMPETENCY-BASED ASSESSMENT PADA PERANCANGAN ALAT PENILAIAN KINERJA PRAKTIK MAKING BED DI HOUSEKEEPING DEPARTMENT - Rohaeni, Neni; Jubaedah, Yoyoh; Rahmah, Audina Adila (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
This study is based on the assessment of making bed practice that used in Housekeeping Vocational High School has not been designed in accordance with Standard Operasional Procedures in the hotel, so the ability of learners in the practice of making beds is not measured accurately.The research aimed at: (1) analyzing the need for performance assesment for bed making practices based on hotel Standard Operasional Procedures; (2) designing assessment of making bed practices based on hotel SOP consist of preparation stage, process and result of practice of making bed, and (3) take feasibility test of design assesment of making bed practice that based on housekeeping department SOP through expert judgment. This research used ADDIE approach which includes Analysis and Design. Data collecting techniques used interviews, observations and expert judgment. The result of the research shows that: (1) the analysis of the assessment for making bed practice used in the SMK has not been referring to the Housekeeping Departmnet Standard Operasional Procedures, so that this finding becomes a necessity in designing the assessment of making bed practice, (2) design of the assessment is a check list which consist of several aspects from the preparation stage, the process to the result of the practice of making bed, (3) the activities of expert judgment conducted by three experts ,they are Academic in the field of Hospitality, Teacher of Preparing Guest Room, and Practitioner in Hotel. The result of the expert judgment activity is the assessment of making bed practice design is feasible to implemented in the subjects of preparing the guest room. The recommendation of this research can be followed up by implementing assessment tool on the practice of making bed at Housekeeping Vocational High School and especially for job performance on housekeeping department expertise. Abstrak Penelitian ini dilatarbelakangi oleh adanya masalah pada alat penilaian kinerja praktik making bed yang digunakan di SMK Akomodasi Perhotelan belum dirancang sesuai dengan SOP Housekeeping Department, sehingga kemampuan peserta didik dalam melakukan praktik making bed tidak terukur secara akurat. Penelitian ini bertujuan untuk: (1) menganalisis kebutuhan alat penilaian kinerja praktik making bed, (2) merancang alat penilaian kinerja praktik making bed berdasarkan SOP Housekeeping department yang meliputi tahap persiapan, proses dan hasil praktik making bed, dan (3) melakukan uji kelayakan rancangan alat penilaian kinerja praktik making bed yang sesuai SOP Housekeeping department melalui kegiatan expert judgment. Penelitian ini menggunakan pendekatan ADDIE. Teknik pengumpulan data menggunakan wawancara, observasi dan kegiatan expert judgment. Hasil penelitian menunjukan bahwa: (1) analisis alat penilaian kinerja praktik making bed yang digunakan di SMK belum mengacu pada SOP Housekeeping department, sehingga temuan ini yang menjadi kebutuhan dalam merancang alat penilaian kinerja praktik making bed, (2) Alat penilaian kinerja praktik dirancang dalam bentuk skala penilaian berupa pedoman observasi yang meliputi tahap persiapan, proses dan hasil praktik making bed, (3) kegiatan expert judgment dilakukan oleh tiga orang ahli yaitu, Akademis di bidang Perhotelan, Guru mata pelajaran Menyiapkan Kamar Tamu, dan Praktisi di bidang Perhotelan. Hasil dari kegiatan expert judgment rancangan alat penilaian kinerja praktik making bed dinyatakan layak untuk diimplementasikan pada mata pelajaran menyiapkan kamar tamu. Rekomendasi dari penelitian ini dapat ditindak lanjuti dengan cara mengimplementasikan alat penilaian pada praktik making bed di SMK Akomodasi Perhotelan dan praktik kerja industri di Housekeeping Depatment.